A preliminary propulsive performances evaluation for an oil tanker to meet EEDI challenge - Mihaela Amoraritei (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding, 2019)
To control CO2 emissions from ships, the International Maritime Organization (IMO) has introduced a mandatory technical measure for new ships: the Energy Efficiency Design Index (EEDI). The paper presents a preliminary evaluation of the propulsive performances for a 30000 tdw oil tanker, complying with the EEDI regulations. Ship resistance and propulsive power have been computed and several main diesel engines have been selected. For every study case, an optimal efficiency propeller has been designed and the Energy Efficiency Design Index has been calculated.